The phenomenon of inherent rhythms in East and Central African instrumental music - Kubik, Gerhard (International Library of African Music, 1962)
African composers take advantage in a marvellous way of a psycho-acoustic fact. The human ear - like the eyes - does not perceive isolated particles but always a "gestalt". In a sequence of notes with large intervals the ear is inclined to pick out those of approximately the same level of pitch, and group them together separately. If this sequence of notes is, moreover, rhythmically regular, perception in different conflicting "gestalten" is enormously stimulated. This gestalt-psychological element plays a great part in listening to and composing some kinds of African instrumental music.
Keywords: Africa; Ethnomusicology; Composition (Music); African Music; Musical Meter; Musical Rhythm